THE IMPACT OF TASK-BASED LANGUAGE TEACHING (TBLT) ON ENHANCING COMMUNICATIVE COMPETENCE IN EFL CLASSROOMS - Berdiqulova Mahbuba Erkinjon qizi; Mehmonova Umidabonu (TADQIQOTLAR, 2026)
ABSTRACT This research paper investigates the profound impact of Task-Based Language Teaching (TBLT) on the development of communicative competence among English as a Foreign Language (EFL) learners. In an era where linguistic accuracy often takes a  backseat  to  functional  fluency,  TBLT  emerges  as  a  bridge  between  theoretical knowledge and practical application. The study compares the traditional Presentation-Practice-Production (PPP) model with the TBLT framework developed by Jane Willis. By analyzing student engagement, fluency, and cognitive load, the paper argues that TBLT  provides  a  more  authentic  environment  for  language  acquisition.  Results indicate  that  students  taught  via  TBLT  demonstrate  higher  confidence  and  a  more robust ability to navigate unpredictable communicative situations.